To find the derivative of the function s we can use the two following approaches:
0. Product rule.
,
1. Using trigonometric identities.
Product rule.
We know that the product rule states that:
![(d)/(dx)(fg)=f^(\prime)g+fg^(\prime)](https://img.qammunity.org/2023/formulas/mathematics/college/bh7elyclwmqjrlti173n0m2i0yj32m2c11.png)
Using this rule in this case we will have:
![\begin{gathered} (ds)/(d\theta)=(d)/(d\theta)(200\sin\theta\cos\theta) \\ =200(d)/(d\theta)(\sin\theta\cos\theta) \\ =200(\cos\theta(d)/(d\theta)\sin\theta+\sin\theta(d)/(d\theta)\cos\theta) \\ =200(\cos\theta\cos\theta+\sin\theta(-\sin\theta)) \\ =200(\cos^2\theta-\sin^2\theta) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/8e9zhivbu32mkyqmatvhmlbklue45vcemw.png)
Therefore, using the product rule, we have that:
![(ds)/(d\theta)=200(\cos^2\theta-\sin^2\theta)](https://img.qammunity.org/2023/formulas/mathematics/college/tfdqcl7749ntr7ts6i46x31iehtvfx5t3o.png)
Using trigonometric identities.
We can also calculate the derivative if we remember that:
![\sin2\theta=2\sin\theta\cos\theta](https://img.qammunity.org/2023/formulas/mathematics/college/2j47s5redjgfwpzou4x94cs8k4czywfvsv.png)
Then, in this case we have:
![\begin{gathered} (ds)/(d\theta)=(d)/(d\theta)(200\sin\theta\cos\theta) \\ =100(d)/(d\theta)(2\sin\theta\cos\theta) \\ =100(d)/(d\theta)\sin2\theta \\ =100(2\cos2\theta) \\ =200\cos2\theta \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/fenp5hno626lxtfyjez4iybi9zoz41xh46.png)
Therefore, using trigonometric identities, we have that:
![(ds)/(d\theta)=200\cos2\theta](https://img.qammunity.org/2023/formulas/mathematics/college/m3j3429rmgckj2nirwsss97h0r3xzphxhv.png)
Note: Both results are equivalent, to prove it we just need to remember that:
![\cos^2\theta-\sin^2\theta=\cos2\theta](https://img.qammunity.org/2023/formulas/mathematics/college/l7xn4cp8dgycj4dd669ob34w5akodrv894.png)
If we use this identity in the first result we get the second one.